2012
DOI: 10.1093/rheumatology/kes075
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcomes of total knee replacement surgery

Abstract: This study identified clinically important predictors of attained pain/function post-TKR. Predictors of pain were not necessarily the same as functional outcomes, which may be important in the context of a patient's expectations of surgery. Other predictive factors need to be identified to improve our ability to recognize patients at risk of poor TKR outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
333
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 315 publications
(358 citation statements)
references
References 33 publications
17
333
1
7
Order By: Relevance
“…Dissatisfaction ranged from 7.5% to 28.3% (median, 18.6%). Psychological health was deemed a significant predictor in satisfaction at a minimum followup of 6 months after TKA in four studies [18,24,27,44]; another study attributed patient dissatisfaction to postoperative stiffness, but did not comment on the effect of mental health state of patients [28].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Dissatisfaction ranged from 7.5% to 28.3% (median, 18.6%). Psychological health was deemed a significant predictor in satisfaction at a minimum followup of 6 months after TKA in four studies [18,24,27,44]; another study attributed patient dissatisfaction to postoperative stiffness, but did not comment on the effect of mental health state of patients [28].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining six studies did not examine these states specifically but showed that lower preoperative mental health scores had similar postoperative associations [8,9,13,27,46,47,50]. Pain scores in the patient population with anxiety, depression, or lower mental health scores were elevated at baseline and at all assessment points [13,27,28,34,37,47,50] for up to 2 years in one study [34 ]. Lingard and Riddle [34] estimated the effect to be 3 to 5 points lower on the 20-point pain component of the WOMAC, indicating worse pain in the group of patients with lower mental health scores.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have also demonstrated that pain‐at‐rest and pain‐on‐movement differ in hip and knee patients. This highlights the importance of distinguishing between these 2 types of pain in research studies, and the need to explore if this distinction can improve the poor ability of statistical models to predict which patients are at risk of developing chronic postsurgical pain 37. There is also a need for further research to understand the pain mechanisms driving these different associations and to investigate whether interventions have different effects in hip and knee OA.…”
Section: Discussionmentioning
confidence: 99%